2018
DOI: 10.1002/adfm.201805001
|View full text |Cite
|
Sign up to set email alerts
|

Realization of 16.9% Efficiency on Nanowires Heterojunction Solar Cells with Dopant‐Free Contact for Bifacial Polarities

Abstract: Low-cost and efficient interfacial layer construction with the required charge selectivity and compatibility is necessary for nanostructured solar cells, and the proper integration of the interfacial layer with the light-trapping system is required to improve the power conversion efficiency of the cell. Herein, low-cost Si nanowires-based solar cells with tunneling heterojunctions are developed by the deposition of MoO x and spin-coating of Cs 2 CO 3 as the carrier-selective layers. The power conversion effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Six O atoms are octahedrally coordinated with each Mo atom arranged into intertwined dual layers, which are fitted via van der Waals forces. [34,35] While in our study, the grazing-incidence X-ray diffraction (XRD) measurements confirm that the as-prepared 30 nm MoO x (on glass) is an amorphous phase. The hump at 25 o is contributed by the glass substrate.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Six O atoms are octahedrally coordinated with each Mo atom arranged into intertwined dual layers, which are fitted via van der Waals forces. [34,35] While in our study, the grazing-incidence X-ray diffraction (XRD) measurements confirm that the as-prepared 30 nm MoO x (on glass) is an amorphous phase. The hump at 25 o is contributed by the glass substrate.…”
Section: Resultssupporting
confidence: 66%
“…Recently, we have observed this phenomenon in Si solar cells. [35,39] This charge transfer creates interfacial polarization, which induces the FEP by efficient separating photogenerated carriers and reducing the probability of Shockley-Read-Hall (SRH) recombination at the heterointerface. [40] Thus, we argue that the FEP caused by the MoO x interlayer may domain the photovoltaic improvement.…”
Section: (4 Of 10)mentioning
confidence: 99%
“…In this scheme, spheroidal silica and titania nanoparticle bilayers are present on top of the cell surface which confines the incident light into the solar cell through whispering gallery modes supported by silica nanoparticles and subsequent forward scattering into the high index absorber substrate by titania nanoparticles. Recently, it was demonstrated that semiconductor nanowire and nanotube heterojunctions can be employed for photovoltaic applications to enhance the light‐trapping capability as well as the electrical properties of solar cells . In these solar cells, the vertical junctions of radial diodes provide a charge carrier collection path separated from the photon‐absorbing layer thickness, allowing the carrier's collection along the radial direction, which results in the minimal recombination within the bulk semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] Furthermore, more integrated devices with multifunctionalities have been investigated from both proof-of-concept and nanosystem integration perspectives. [21][22][23][24] Additionally, the nanowire configuration frequently exhibits reinforced mechanical properties compared to other configurations, including enhanced fracture resistance under bending (tensile) deformation and a tunable elastic modulus, making it advantageous for application in flexible devices and free-standing probes integrated with other functionalities. 25,26 To date, strategies for the controllable synthesis of nanowires with respect to their morphology, size, and crystal phase have been significantly developed.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their abundant electrical, photonic, and mechanical properties, semiconductor nanowires, including Si, Ge, metal oxides, and III‐V and II‐VI compounds, have undergone great progress in the fields of electronics, subwavelength light waveguiding, and sensing (for photoelectric, chemical, and biological purposes) . Furthermore, more integrated devices with multifunctionalities have been investigated from both proof‐of‐concept and nanosystem integration perspectives . Additionally, the nanowire configuration frequently exhibits reinforced mechanical properties compared to other configurations, including enhanced fracture resistance under bending (tensile) deformation and a tunable elastic modulus, making it advantageous for application in flexible devices and free‐standing probes integrated with other functionalities …”
Section: Introductionmentioning
confidence: 99%